Retracing images : visual culture after Yugoslavia - Šuber, Daniel; Karamanić, Slobodan (Balkan studies library ;, 2012)
Drawing on visual materials (film, art, graffiti, street-art, public advertisement, memorials), the essays of this collection offer detailed views on the cultural and political dynamics that preceded and emerged in the wake of the Yugoslav conflicts of the 1990s.